Texture, color, lipid oxidation and sensory acceptability of gamma-irradiated marinated anchovy fillets - Tomac, Alejandra (2015)
The effect of gamma irradiation (0, 2, 3 and 4. kGy) on vacuum-packed marinated anchovy fillets was analyzed for their texture, color, lipid oxidation and sensory acceptability after 10 months under refrigeration. Marinated (3% acetic acid, 10% sodium chloride and 0.2% citric acid) Engraulis anchoita fillets were vacuum-packed and irradiated with a cobalt-60 source at a semi-industrial irradiation facility. The irradiation caused a slight increase in hardness values regardless of the applied dose but maintained a consistent texture over the 10 months, even though the control samples softened, most likely due to degradation. This hardness increase did not affect the textural sensory acceptability. Irradiation did not modify the color but still reduced color changes during storage, benefitting the product's quality. TBARS was increased in every sample throughout storage, but irradiation decreased these values. Sensory acceptability was not affected by gamma irradiation. Therefore, gamma irradiation could be successfully applied to this type of product for the purpose of shelf-life extension.